Kondisi Information Overload pada Mahasiswa IAI AL-AZIS Akibat Penggunaan Media Sosial yang Tidak Sehat - Apriyani Alfinawardani Nuralmi; Muhammad N. Abdurrazaq; Imang Maulana (Jurnal Syntax Admiration, 2024)
In the ever-growing digital era, social media has become an inseparable part of students' daily lives, which ultimately gives rise to the information overload phenomenon. This research aims to determine the condition of information overload among IAI AL-AZIS students due to unhealthy use of social media, as well as its impact on their academic and personal aspects.The research method used is qualitative. Data was collected through interviews, observation, and documentation with 14 students at the Al-Zaytun Indonesian Islamic Institute from various study programs. The research results show that students experience information overload caused by unhealthy use of social media, such as difficulty in processing diverse and complex information, as well as confusion in selecting and assessing the truth of information. Apart from that, excessive use of social media has an impact on social media users themselves, both academically, personally, and socially. To minimize this impact, IAI AL-AZIS students apply strategies such as managing time and applying the principles of Islamic teachings, as in Surah Al-Hujurat verse 6, such as tabayyun, critical thinking, and being careful in spreading information whose truth is not yet known.